The Relationship Between Pregnancy Exercise and Back Pain in Third Trimester Pregnant Women at Klinik Pratama Jaya in 2025 - Anita Pratin Siahaan; Ade Ira Zahriany (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
The purpose of this study was to determine the relationship between pregnancy exercise and back pain among third trimester pregnant women at Klinik Pratama Jaya in 2025. Back pain is a common complaint during pregnancy, particularly in the third trimester, due to physiological and anatomical changes. As a non-pharmacological intervention, pregnancy exercise is believed to help alleviate discomfort, especially in the lower back region. This study aims to contribute empirical evidence regarding the effectiveness of pregnancy exercise in reducing back pain intensity during late pregnancy. Materials and methods. This research employed a quantitative method with a cross-sectional design. The sample consisted of 35 third trimester pregnant women selected through total sampling. Data were collected using questionnaires assessing participation in pregnancy exercise (regular or irregular) and the intensity of back pain (mild, moderate, severe, very severe). The data were processed through stages including editing, coding, tabulation, and statistical analysis using the Chi-square test with a significance level of 0.05. Results. Findings showed that 54.3% of respondents participated in pregnancy exercise regularly, while 45.7% did not. The majority of respondents reported mild pain (48.6%), followed by moderate and severe pain (22.9% each), and very severe pain (5.6%). The Chi-square test revealed a significant relationship between pregnancy exercise and back pain (p = 0.002 < 0.05), indicating that regular participation in pregnancy exercise is associated with reduced intensity of back pain. Conclusions. Pregnancy exercise has a significant impact on reducing back pain in third trimester pregnant women. These findings suggest that pregnancy exercise should be promoted as a safe, effective, and low-cost strategy to improve maternal comfort and well-being during late pregnancy.